2010
DOI: 10.1093/mp/ssp102
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana HAK5 K+ Transporter Is Required for Plant Growth and K+ Acquisition from Low K+ Solutions under Saline Conditions

Abstract: K(+) uptake in the high-affinity range of concentrations and its components have been widely studied. In Arabidposis thaliana, the AtHAK5 transporter and the AtAKT1 channel have been shown to be the main transport proteins involved in this process. Here, we study the role of these two systems under two important stress conditions: low K(+) supply or the presence of salinity. T-DNA insertion lines disrupting AtHAK5 and AtAKT1 are employed for long-term experiments that allow physiological characterization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
145
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 43 publications
4
145
0
1
Order By: Relevance
“…NO is a plantendogenous messenger involved in growth and multiple stress responses (14,44,48). Here, we show that NO negatively regulates the absorption of K + , an ion that has marked impacts on cell metabolism, plant growth, and stress adaption (26,52). Plant growth rate correlates with K + uptake (26,53), and less K + uptake will retard plant growth.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…NO is a plantendogenous messenger involved in growth and multiple stress responses (14,44,48). Here, we show that NO negatively regulates the absorption of K + , an ion that has marked impacts on cell metabolism, plant growth, and stress adaption (26,52). Plant growth rate correlates with K + uptake (26,53), and less K + uptake will retard plant growth.…”
Section: Discussionmentioning
confidence: 93%
“…Studies showed that under K + -deprived saline conditions where plant K + contents diminished dramatically, AKT1-mediated K + efflux was promoted, and AtHAK5 transcription was also largely reduced (52), suggesting that the regulation of K + contents in this situation happens at various aspects. The possible effect of NO on AtHAK5 transporter, especially in low K + conditions, remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AKT1 probably acts as K + sensor because it has dual-affinity activity and its phosphorylation based regulation by CIPK23 similar to the NO 3 − sensor, i.e., CHL1 transporter (Schroeder and Fang 1991;Li et al 2006;Xu et al 2006). In plants, the hyperpolarization (Maathuis and Sanders 1994;Nieves-Cordones et al 2010) and depolarization (Spalding et al 1999) of membrane potential at low and high external K + concentration respectively may act as K + sensing mechanisms. Plant undergoes both short-and long-term responses after signal perception (Schachtman and Shin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis (Arabidopsis thaliana), the high-affinity K + transporter HAK5 (Rubio et al, 2000;Nieves-Cordones et al, 2010) and the Shaker inward K + channel AKT1 (Lagarde et al, 1996;Hirsch et al, 1998;Spalding et al, 1999;Ivashikina et al, 2001) have been considered two major components that conduct K + uptake in root cells under low-K + (LK) conditions (Gierth et al, 2005;Pyo et al, 2010;Nieves-Cordones et al, 2014). The transcription of HAK5 is induced by K + deficiency (Gierth et al, 2005), which is an important mechanism in plant responses to LK stress .…”
mentioning
confidence: 99%